One, few or many? An integrated framework for identifying the items in measurement scales - Malhotra, Naresh K. (2015)
Churchill (1979) proposed a detailed procedure for the development of better multi-item measures that has become popular. Recently, however, many scholars have challenged this dominant paradigm. They argue that, in many marketing contexts where the target construct has a precise and concrete definition, long multi-item measures can be substituted by shorter measures with fewer items, or even single-item measures. This has resulted in the controversy around the relative superiority of single- versus multi-item scales. We review the extant literature to summarise various arguments in favour of (or against) multi-item and single-item measures, respectively. Moreover, we propose an integrated framework for developing a new scale, reducing long multi-item scales to shorter multi-item measures or to single-item measures, or to expand an existing short (single-item) scale. The significant contributions of this paper to the literature are identified.